E-logpO2 diagrams for ironmaking by molten oxide electrolysis. (1st September 2017) - Judge, W.D.; Allanore, A.; Sadoway, D.R.; Azimi, G.
Abstract: Molten oxide electrolysis is a promising approach to sustainable iron extraction, where direct electrolytic decomposition of iron ore proceeds to yield liquid metallic iron and pure oxygen gas. Here, through fundamental investigations, we constructed thermodynamic E -log p O2 diagrams for systems containing iron and its oxides to elucidate the chemistry of the electrolysis cell at various electric potentials and oxygen partial pressures. Two isotherms, 1473 and 1873 K, were investigated, representing the conditions of the frozen electrolyte sidewall and molten oxide electrolyte in the electrolysis cell, respectively. Stability regions of solid and liquid oxides were determined and the effect of electric potential and oxygen partial pressure on their stoichiometry was explored. The results would enable further development of the electrolysis cell through providing a means for improving the design of the electrolyte to maximize current efficiency.